The zero-waste lifestyle : live well by throwing away less - Korst, Amy, 1984- (Ten Speed Press, 2012)
"A practical guide to generating less waste, featuring meaningful and achievable strategies from the blogger behind The Green Garbage Project, a yearlong experiment in living garbage-free. You don't have to be a tree hugger to benefit from zero-waste living. The average American tosses out nearly five pounds of trash every day, yet studies show the more we buy, the less happy we are. In The Zero-Waste Lifestyle, Amy Korst shows us how to have a happier, healthier, more sustainable life by sharing the lessons she learned while going waste-free for an entire year. Each chapter presents easy steps that anyone can take to create less trash: from composting and retaking reusable containers to the grocery store to burning clean organic materials; upcycling, downcycling, and recycling goods; and more"--